Non-amide based zwitterionic poly(sulfobetaine methacrylate)s as kinetic hydrate inhibitors. (16th January 2021) - Zhang, Qian; Kelland, Malcolm A.; Lewoczko, Evan M.; Bohannon, Caleb A.; Zhao, Bin
Highlights: Zwitterionic poly(sulfobetaine methacrylate)s were investigated as kinetic hydrate inhibitors for the first time. The zwitterionic poly(sulfobetaine methacrylate) with N -(n-hexyl) groups gave the best KHI performance. Compared to polyamides, KHI performance shows much less improvement with increasing concentration. Abstract: Applying kinetic hydrate inhibitors (KHIs) to avoid the pipeline blockage caused by hydrate formation in gas and oil industry is a comparatively effective and cost-saving method. The main ingredients in most KHIs are water-soluble polymers containing repeating amide group units, placed structurally close to hydrophobic groups. In this report we have synthesized a class of non-amide polymers, zwitterionic poly(sulfobetaine methacrylate)s, and investigated them as KHIs for the first time. Results show that the best zwitterionic polymers have good KHI efficacy with the key performance parameter being the length of the alkyl chain on the monomer unit side chains. Copolymer of the zwitterionic monomers and N -isopropylmethacrylamide (NIPMAM) gave much better increase in KHI performance with increasing concentration than the zwitterionic homopolymers. This result together with other related studies suggests that strong hydrogen-bonding groups like amide or amine oxide groups are important for high KHI performance. Reasons for this are discussed.